Fibras funcionais de linhaça como pró-nutriente para tilápia do Nilo - Kowalski, Éverton Augusto (2021)
The effects of including increasing levels of a combination of soluble and insoluble fractions, in a 1:4 ratio of functional fibers of linseed were evaluated in Nile tilapia juveniles (Oreochromis niloticus) on performance efficiency parameters, body composition and deposition of nutrients, body yield and digestive indices, digestive enzymes, plasma parameters, hepatic metabolites and production of short-chain fatty acids (SCFA). For this, the linseed fiber pro-nutrient was added at five increasing levels (00, 20, 40, 60, 80 g/kg) to the diet of the tilapia (13,33 ± 0,13 g), through a biological trial for 60 days, in a water recirculation system. During this period, the fish were fed until apparent satiety, three times a day. At the end of the experimental period, the fish were fasted for 18 hours before data collection. The experimental design was completely randomized, with five treatments and four replications (500 fish). Data were subjected to analysis of variance and means compared by Tukey test (P<0,05). The results indicate that linseed functional fiber pro-nutrient did not influence the performance efficiency of fish, similarly, in the digestive, enzymatic, plasmatic and hepatic metabolites indexes. However, higher levels of fat, dry matter and higher production of short-chain fatty acids by the intestinal microbiota were verified, with inclusion 60 g/kg of the pro-nutrient in the diet of tilapia juveniles. As well as, greater deposition of body fat with the level of 20 g/kg of the pro-nutrient. In conclusion, the linseed fiber pro-nutrient possibly acted in energy partitioning, changing the body composition of tilapia juveniles, however other studies must be conducted to understand the relationship of the fiber pro-nutrient with the species in question.